7-Chloro-1,5-dipropargyl-1H-1,5-benzodiazepine-2,4(3H,5H)-dione - Dardouri, R.; Rodi, Y.K.; Saffon, N.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The seven-membered ring of the title compound, C15H11ClN2O2, adopts a boat-shaped conformation (with the C atoms of the fused-ring as the stern and the methylene C atom as the prow). The N atoms exists in a trigonal-planar coordination; one of the acetylenic H atoms forms a C-H center dot center dot center dot O hydrogen bond to the O atom of an adjacent molecule, generating a linear chain along a body diagonal.